Perception, identity and meaning in the social and ritual construction of landscape: The Lihue Calel Hills, La Pampa, Argentina - Curtoni, Rafael; Beron, Monica (Revista Chilena de Antropología, 2011)
This paper discusses how the social construction of landscape and the sense of identity and territoriality can emerge in relation to a ritual space. Through the analysis of monumental constructions or arrangements of rocks, its topographical connection and the location of cave paintings and cemeteries, a ritualized landscape may be defined. The archaeological information of the Sierras Lihué Calel is employed for this. This area is located in the western sector of the pampean region of Argentina.